The Philosophy of Julian Tuwim’s Stanza - Matywiecki, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The aim of the article is to argue that Tuwim’s way of conceptualizing both the world and poetry was based on the principle of stanza. In his opinion, the entire world and our experience of it reach us in a stanzaic form. In Tuwim’s writing the stanza could be compared to an atom of poetic structure. It also builds our primary consciousness of language. The stanzaic structure of our poetic and linguistic experience imposes an order on the universe as we see it. Tuwim hears and thinks his world as a stanza.